THE EFFECT OF IMPLEMENTATION OF CANVA BASED DIGITAL HANDOUT DEVELOPMENT ON PANCASILA PHASE B EDUCATION SUBJECT USING THE RICOSRE LEARNING MODEL IN PRIMARY SCHOOL - Maya Novitasari; L.R Retno Susanti; Evy Ratna Kartika Waty; Makmum Raharjo (Jurnal Cakrawala Pendas, 2024)
The covid-19 pandemic has has a major influence on obstacle in the learning process which has resulted in a decrease in learning outcome. This obstacle refers to the lack of teaching materials that support the learning process, while the learning process must be carried out online. Therefore, it is necessary to use technology that can make it easier fpr educators to present material and give students the freedom to carry out the learning process wherever and whenever. Considering that online-based technology has a high level of flexibility. The research aims to explain the effect of implementing Canva based digital handout development on Pancasila Phase B Education subject with the Reading, Identifying, Construction, Solving, Reviewing, Extending (RICOSRE) learning model in primary schools. The subjects of this research were fourth grade students at state primary school 81 Palembang. The research method used is Research and Development with reference to the Rowntree research model. Data collection techniques were carried out through observation, interviews, questionnaires and group discussion forums (FGD). The research results refer to the increase in learning outcomes shown through the pretest with an average pretest score of 61.66% and an average posttest of 90.33%, while the N-Gain results show 0.76 which is in the high category. This shows that there is an increase in learning outcome of 28.7% and is included in the very effective category. Based on the research results, it can be concluded that the implementation of Canva-based digital handout development can have an influence that refers to improving learning outcomes in Pancasila Phase B Education subject.